Labour market regimes and unemployment in OECD countries - Sturn, Simon (Düsseldorf, 2011)
"Until now there exists no consensus view on the determinants of unemployment. Whereas some empirical papers find that mainly labour market institutions explain unemployment, others argue that this correlation is not robust. One explanation for these contradictory results is that labour market institutions affect unemployment in varying labour market regimes differently. Due to institutional complementarities and a trade-off between external and internal flexibility, certain labour market institutions show different impacts on unemployment depending on the general institutional arrangement. Support for this is found when testing for the impact of labour market institutions on unemployment in different labour market regimes with panel data for 20 OECD countries in the period 1982 to 2003. While external labour market flexibility shows the expected impact on unemployment in some countries, this is not the case in corporatist countries, which are characterised by high internal flexibility and good labour relations. Taking account of the regime is therefore crucial for successful labour market policy. Additionally, high real interest rates and restrictive monetary and fiscal policy in downturns are found to increase unemployment, suggesting that policy makers should react actively to economic downturns."